Retail Accounting and Financial Control. - Seiler, Robert E. (The Accounting Review, 1978)
Abstract Reviews the book "Retail Accounting and Financial Control," 4th ed., by Louis C. Moscarello, Francis C. Grau and Roy C. Chapman.